Exploring important factors influence demand for flexible windows: a quantitative study of Universiti Technologi Malaysia staff / Vahid Moghimi and Mahmud Mohd Jusan - Moghimi, Vahid; Mohd Jusan, Mahmud (Universiti Teknologi MARA, Negeri Sembilan, 2013)
The current trend in mass produced housing in Malaysia includes the provision of housing unit which are not easily adaptable to the lifestyle changes of users. Consequently, various architectural elements of housing units including windows are subject to modification. This phenomenon is evident when 42% of the respondents of this research experienced window replacement in their homes. This study has been undertaken with particular focus on users’ reasons for having flexible windows. To achieve this, quantitative surveys were carried out among staff members of Universiti Teknologi Malaysia. The results indicate 74.4% of the users, spread among various social groups, are enthusiastic about having flexible windows installed in their houses. Consideration of this demand for flexible windows reveals that personalized housing and the various levels of environmental comfort shows parallelism. Flexible windows are in demand to fulfil physical and psychological housing needs. By linking the user’s needs to flexible windows, user-congruence environment, hence propagation of sustainable living environment will be improved.